2020
DOI: 10.1002/jcp.30083
|View full text |Cite
|
Sign up to set email alerts
|

Scoparone alleviates hepatic fibrosis by inhibiting the TLR‐4/NF‐κB pathway

Abstract: The aim of this study was to investigate the role of scoparone (SCO) in hepatic fibrosis. For this, we conducted in vivo and in vitro experiments. In vivo rats that were divided into six groups, control, carbon tetrachloride, and colchicine, as well as SCO groups, SCO50, SCO100, and SCO200 treated with 50, 100, and 200 mg/kg SCO doses, respectively. Furthermore, SCO was shown to inhibit Toll‐like receptor‐4 (TLR‐4)/nuclear factor kappa‐B (NF‐κB; TLR‐4/NF‐κB) signals by inhibiting TLR‐4, which in turn downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Inactivated NF-κB is located in the cytoplasm, but when cells are stimulated by cytokines, NF-κB then translocates into the nucleus to activate gene transcription ( 40 ). Studies have previously shown that NF-κB can promote the expression of inflammatory factors IL-1, TNF-α and IL-6 during hepatic fibrosis ( 41 , 42 ). In the present study, western blotting results showed that injection of CFA increased ERK1/2 and p65 protein phosphorylation but lidocaine treatment reversed this.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivated NF-κB is located in the cytoplasm, but when cells are stimulated by cytokines, NF-κB then translocates into the nucleus to activate gene transcription ( 40 ). Studies have previously shown that NF-κB can promote the expression of inflammatory factors IL-1, TNF-α and IL-6 during hepatic fibrosis ( 41 , 42 ). In the present study, western blotting results showed that injection of CFA increased ERK1/2 and p65 protein phosphorylation but lidocaine treatment reversed this.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested that SCO also mitigate hepatic steatosis and fibrosis in NAFLD mice induced by choline deficiency diet (7), which means SCO maybe improve NAFLD by regulating lipid metabolism. Furthermore, our preliminary study also confirmed that SCO could downregulate the expressions of alanine aminotransferase (ALT), aspartate aminotransferase (AST), g-glutamyl transferase (g-GT) in serum, effectively improving liver damage (8). Up till now, although some drugs (such as vitamin E, statins and metformin) have been tried to treat NAFLD, the efficacy is limited (9)(10)(11).…”
Section: Introductionmentioning
confidence: 59%
“…The HFD + SCO 60 group, HFD + SCO 120 group and HFD + Silymarin group were administered intragastrically with SCO (60 mg/kg, 120 mg/kg) and Silymarin (150 mg/kg) for 4 weeks (Figure 1), respectively. The dose of SCO was according to other studies and our previous studies with some adjustments (7,8). At the end of the 12th week, all mice were fasted overnight.…”
Section: Hfd-induced Nafld and Sco Administrationmentioning
confidence: 99%
“…Scoparone, a biologically active ingredient obtained from the Chinese medicinal Artemisia capillaris Thunb, has a wide range of pharmacological effects, such as hypolipidemic and anti-inflammatory properties . In a methionine–choline deficient (MCD) diet-induced NASH mice model, scoparone caused a significant improvement in liver inflammation, steatosis, and fibrosis. , Amelioration of NASH symptoms could be achieved by scoparone through enhanced autophagy in macrophages . Scoparone functioned by inactivating the TGF-β/Smad signaling pathway, thereby significantly inhibiting hepatic stellate cells (HSCs) activation and proliferation to prevent hepatic fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…16 In a methionine−choline deficient (MCD) diet-induced NASH mice model, scoparone caused a significant improvement in liver inflammation, steatosis, and fibrosis. 17,18 Amelioration of NASH symptoms could be achieved by scoparone through enhanced autophagy in macrophages. 19 prevent hepatic fibrosis.…”
Section: ■ Introductionmentioning
confidence: 99%